2018
DOI: 10.1016/j.ejmp.2017.12.022
|View full text |Cite
|
Sign up to set email alerts
|

A novel Hemi-Body Irradiation technique using electron beams (HBIe−)

Abstract: In conclusion, HBIe was proven effective in delivering the prescribed dose to the target area, while protecting the healthy skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…[25][26][27][28] Following previous publications of our experience with the clinical use of electron beam therapy for cutaneous disorders and in particular with TSEB therapy in the management of MF, our study evaluates the effectiveness and toxicity of low dose scheme. [29][30][31] In our patient cohort of 14 patients we demonstrated treatment results similar with those from relevant literature. Although the CR rate was 21.4% the OR rate was 92.4% as 13 out of 14 patients showed clear benefit in skin disease burden.…”
Section: Toxicity Of Treatmentsupporting
confidence: 77%
“…[25][26][27][28] Following previous publications of our experience with the clinical use of electron beam therapy for cutaneous disorders and in particular with TSEB therapy in the management of MF, our study evaluates the effectiveness and toxicity of low dose scheme. [29][30][31] In our patient cohort of 14 patients we demonstrated treatment results similar with those from relevant literature. Although the CR rate was 21.4% the OR rate was 92.4% as 13 out of 14 patients showed clear benefit in skin disease burden.…”
Section: Toxicity Of Treatmentsupporting
confidence: 77%
“…Following previous publications reporting on clinical applications of TSEB, our study also evaluated the effectiveness and toxicity of low dose scheme compared to the standard dose of 36 Gy [26] , [27] , [28] . Even with the very small cohort of 14 patients we demonstrated that the overall response rate for both treatment schedules was excellent (93%).…”
Section: Discussionmentioning
confidence: 99%
“…The upper, middle or, lower half of the skeleton may be irradiated. Both photon beams and electron beams may be used [54,55]. Delivering 6–8 Gy in single fraction results in pain response in 70% of patients after 24–48 h [54].…”
Section: Painful Bone Metastasesmentioning
confidence: 99%
“…Delivering 6–8 Gy in single fraction results in pain response in 70% of patients after 24–48 h [54]. The intensity of pain is reduced significantly, from 8 to 1, according to the visual-analogue scale, and there is a decrease in morphine consumption [54,55]. It is a very convenient treatment type for advanced cancer patients since it involves a short hospital stay and acceptable side effects [54].…”
Section: Painful Bone Metastasesmentioning
confidence: 99%